2017
DOI: 10.7567/apex.10.076502
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly ethanol-developable processes for electron beam lithography using positive-tone dextrin resist material

Abstract: From the viewpoints of the utilization of agricultural resources and advanced use of biomass, this study is aimed at expanding the resolution limits of ecofriendly ethanol-developable processes for electron-beam lithography using a positive-tone dextrin resist material with high hydrophilicity on a cellulose-based underlayer. The images of 20-nm-hole and 40-nm-line patterns with an exposure dose of approximately 1800 µC/cm2 were provided by ecofriendly ethanol-developable processes instead of the common develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…13 Close attention has also been paid to polysaccharides that could be good candidates for commercial photoresist replacement. It was shown that cellulose 4,8 alginate, 14 dextrin, 6 and pullulan 15 can be used as photolithography resists. Nevertheless, the abovementioned polysaccharides need to be chemically modified to acquire electro-or photosensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…13 Close attention has also been paid to polysaccharides that could be good candidates for commercial photoresist replacement. It was shown that cellulose 4,8 alginate, 14 dextrin, 6 and pullulan 15 can be used as photolithography resists. Nevertheless, the abovementioned polysaccharides need to be chemically modified to acquire electro-or photosensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The reported water-developable biomass resist material was used in an electron beam nanolithography tool (CABL-8000TPU, Crestec), and a reactive ion etcher RIE-10NR (Samco) was utilized for creating the quartz mold to draw 900-nm lines. [32,33] The patterning of the non-solvent-permeable quartz mold was performed for 10 min using tridecafluro-1,1,2,2-tetrahydrooctyld imethylchlorosilane after the surface was exposed to electron beam (EB) irradiation with energy of 90 kV. Compact electron beam system (EC90/10/50LS-T, Iwasaki Electric) was used to obtain anti-adhesion between the quartz mold and the patterning materials.…”
Section: Methodsmentioning
confidence: 99%
“…The first particular solution to mention is a sugar‐based negative tone resist [ 146 ] that facilitated water‐based development of the resist film with a 100 nm resolution at 18 µC cm −2 (30 kV). Another example, natural linear polysaccharide pullulan, [ 151 ] demonstrated a resolution of 100 nm at a sensitivity of 10 µC cm −2 . This negative tone resist is compatible with both EUV and e‐beam exposure.…”
Section: Patterning Approachesmentioning
confidence: 99%
“…Another example of polysaccharides, dextrin derivatives, [ 151 ] demonstrated a high resolution (20 nm) positive tone ethanol‐developable resist behavior with the sensitivity of roughly 1800 µC cm −2 (125 kV). However, the obtained derivative was not water‐soluble, which limited application toward bio‐organic materials.…”
Section: Patterning Approachesmentioning
confidence: 99%